Waqf Governance Reform: The Mandate for Digitalization of Nazhir Reporting for Accountability in East Java - Dwi Agung Maryaningsih (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This Policy Paper aims to identify and formulate policy solutions to fundamental problems in waqf governance in East Java, which has significant asset potential. The main problem identified, through an analysis of Urgency, Seriousness, and Growth (USG), is the constraints on transparency and accountability in Nazhir reporting. The root of this problem stems from the absence of a local regulatory mandate requiring integrated digital reporting (Mandated Disclosure) and Nazhir's low compliance with Waqf Accounting Standards (PSAK 112). This condition is exacerbated by the lack of institutional synergy between the East Java Regional Office of the Ministry of Religious Affairs and the Indonesian Institute of Islamic Studies (BWI) in digital infrastructure integration (IT Governance), thus increasing the risk of moral hazard. This policy formulation uses a qualitative, policy-based analysis with a framework of Agency Theory, Transaction Cost Economics, and Institutionalism, supported by the Maslahah Mursalah concept and Waqf Core Principles. This analysis process produces a single, most effective policy recommendation: the Decree of the Head of the East Java Regional Office of the Ministry of Religious Affairs on Mandatory Integrated Digital Waqf Reporting. This coercive mandate aims to force all Nazhirs to use a single platform (SIWAK) for PSAK 112 reporting, effectively building a transparent and accountable E-Trust Waqf Ecosystem.